Trade openness, trade costs and growth: Why sub-Saharan Africa performs poorly - Jennifer Mbabazi; Chris Milner; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2006)
The principal aim of this paper is to identify, in the context of the relationship between openness and growth, factors that can account for the poor growth performance of subSaharan African (SSA) countries. Including inequality as a broad measure of policy distortions, attention focuses on policy and non-policy barriers to trade, indicators of openness and resource endowments. The empirical analysis uses cross-section and panel econometric techniques to investigate the links between growth, inequality and openness for a sample of 44 developing countries over 1970-95. There are four broad conclusions. First, within the sample, there is a low correlation between initial GDP and inequality. Second, inequality appears to have a robust negative effect on growth in the long run but not in the short run. Third, we find consistent evidence that openness is positively associated with growth, and some evidence that trade liberalisation tends to offset or dampen the negative effect of inequality on growth. Finally, Africa does appear to be different; the especially poor SSA growth performance can be explained by the combination of low levels of openness, high natural barriers to trade (especially high costs of transport to distant dynamic markets) and export dependence on primary commodities.
Keywords: F14; O10; 330; Openness; Transport Costs; Trade and Growth; Sub-Saharan Africa